1989
DOI: 10.3406/cea.1989.1643
|View full text |Cite
|
Sign up to set email alerts
|

Between the Sea and the Lagoons: The Interaction of Maritime and Inland Navigation on the Precolonial Slave Coast

Abstract: R. Law — Entre mer et lagune : les interactions de la navigation maritime et continentale sur la Côte des Esclaves avant la colonisation. Sur la Côte des Eslaves, c'est-à-dire sur la portion de la côte d'Afrique de l'Ouest comprise entre la Volta et la rivière Lagos, les peuples autochtones, avant l'arrivée des Européens, ne connaissaient pas la navigation maritime. Cependant, les lagunes qui s'étendent parallèlement à la côte étaient parcourues par des embarcations, et une économie maritime originale, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The canoemen were also employed in such great numbers that they established their own communities. In Aneho (located today within Togo), for example, the Fante canoemen established a community with their own leaders probably as early as 1650 [29]. Their type of organization was quite similar to today's migrant fishing communities.…”
Section: Case Studies In Ghana and Nigeriamentioning
confidence: 99%
See 2 more Smart Citations
“…The canoemen were also employed in such great numbers that they established their own communities. In Aneho (located today within Togo), for example, the Fante canoemen established a community with their own leaders probably as early as 1650 [29]. Their type of organization was quite similar to today's migrant fishing communities.…”
Section: Case Studies In Ghana and Nigeriamentioning
confidence: 99%
“…People have been fishing in rivers and lagoons along the coast of Ghana long before Europeans started writing about it in the 15th century. However, it is reported that marine fishing and coastal trade by sea developed mainly with the arrival of European traders [29]. The report postulated that because of lack of natural harbors in West Africa, the Europeans hired fishermen as canoemen to transport people and goods from their ships across the rough surf to the beaches, and vice-versa.…”
Section: Case Studies In Ghana and Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…1700 after Law 1991:232 4 It is beyond the scope of this paper to present an atlas of the historiography of the region or Hueda. For reviews, see Akinjogbin (1967), Bay (1998), and Law (1989aLaw ( , b, 1990Law ( , 1991Law ( , 2004. This paper builds on efforts (e.g., Bay 2008;Blier 1995a) to explore and foreground the material culture of Vodun and specifically describe the active role that such objects played in mediating and producing cultural processes.…”
mentioning
confidence: 98%
“…During the early documented history of the region, towns, often with palaces near their centers, served as locales where international transactions were negotiated. To feed the soaring demand for captives, local kings and elites relied not only on local raids, but also on longstanding trading networks that linked the Dahomey Gap region to the forest zone located to the east and west, and the Sahel region to the north (Brooks 1993;Law 1989a). The cosmopolitan character of the 17th-and 18th-century trading towns of the region is exemplified by markets containing fine items drawn from throughout the region, and the far reaches of the emerging globalized world (Phillips 1732: 227).…”
mentioning
confidence: 99%